Avaliação da qualidade da cavala (Scomberomorus cavalla) revestida com gelatina da pele do atum (Thunnus albacares) enriquecida com TBHQ - Cerqueira, Davi Araujo (2024)
Global production of marine resources reached 185.4 million tons, producing waste that can be used to create value-added products. Mackerel is a popular species in the Northeast of Brazil, especially in Ceará. While yellowfin tuna generates important waste, such as gelatin from its skin, which has biotechnological potential. This study aims to evaluate the shelf life and quality of mackerel fillets coated with gelatin extracted from tuna skin, glycerol and tert-butylhydroquinone. The gelatin was extracted from cleaning the skins in water and NaCl, followed by treatment with acetic acid and neutralization with NaOH. The skins then underwent alkaline and acid hydrolysis to break down the collagen. In the extraction step, the skins were mixed with water, agitated at 45 °C for 2 hours, filtered, and the obteined solution was lyophilized and ground. After extraction, analyses were conducted to determine gel strength, DSC, FT-IR, color, and centesimal composition. To assess antioxidant activity, four filmogenic solutions with 1% gelatin and different TBHQ concentrations (0.01%, 0.02%, 0.03%) were prepared. The final solution for application contained 1% gelatin, 0.5% glycerol, and 0.03% TBHQ in 2000 mL of distilled water. This solution was applied to mackerel steaks, which were stored at 4 °C and evaluated for quality over 20 days. Results showed that gelatin extracted from tuna skins had a yield of 11.66%. The centesimal composition revealed a high protein content. Gel strength, along with DSC and FT-IR, indicated good mechanical properties for forming the filmogenic solution. Antioxidant activity increased proportionally with TBHQ concentration. This gelatin, with 0.03% TBHQ, was effective in controlling lipid oxidation, maintaining pH stability, acting as a barrier against bacteria, and preserving the color characteristics of the fish. Thus, it can be stated that the action of gelatin with the additive of a synthetic antioxidant in acceptable concentrations, TBHQ, provides extra protection to the fish, coupled with good storage conditions.